2020
DOI: 10.1097/jom.0000000000001918
|View full text |Cite
|
Sign up to set email alerts
|

Injury Correlates Among a National Sample of Women in the US Fire Service

Abstract: Objective: To examine occupational injuries among career women firefighters (FFs). Methods: A national cross-sectional survey assessed injury prevalence, types, frequencies, and predictors. Results: A total of 3012 women career FFs were enrolled in the study. Almost a third (31.7%) reported at least one occupational injury in the past 12 months. The most common injuries were dislocations, sprains, or strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
4
13
1
Order By: Relevance
“…Strains/sprains/muscle pain were the most common injuries identified, followed by dislocations/fractures, and wounds/cuts/bleeds/bruises. This is similar to another sample of female firefighters from the US, who reported predominantly dislocations/strains/sprains, followed by superficial injuries/open wounds ( 13 ). Other injuries, including eye injuries or smoke/gas inhalation, occurred in lower proportions, potentially because protective equipment reduced the risk for these injuries.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Strains/sprains/muscle pain were the most common injuries identified, followed by dislocations/fractures, and wounds/cuts/bleeds/bruises. This is similar to another sample of female firefighters from the US, who reported predominantly dislocations/strains/sprains, followed by superficial injuries/open wounds ( 13 ). Other injuries, including eye injuries or smoke/gas inhalation, occurred in lower proportions, potentially because protective equipment reduced the risk for these injuries.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies have identified that firefighters with a higher-than-normal BMI were three times more likely to file an injury-related compensation claim compared with those of normal BMI ( 20 ). Higher overall good self-rated health, fitness, and exercise have all related to a lower likelihood of sustaining an injury ( 13 ). Low fitness levels among firefighters can increase injury risk ( 20 ), and compromise occupational readiness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations